2011
DOI: 10.1590/s1806-37132011000200014
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia tuberculosa: um estudo de 59 casos confirmados microbiologicamente

Abstract: Objective: To study the clinical, epidemiological, radiographic and endoscopic features of individuals with tuberculous pneumonia. Methods: We evaluated 2,828 consecutive tuberculosis patients treated at a public health center between December of 2005 and February of 2007. Of those, 59 (2.1%) had pulmonary involvement consistent with fistula between a lymph node and a bronchus. Results: Of the 59 patients studied, 43 (73%) were between 20 and 50 years of age, 31 (53%) were male, and 28 (47%) were Black. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For instance, in a cohort of 2228 patients with TB in Brazil, 59 (2%) patients presented with noncavitary pulmonary consolidation, which occurred predominantly in the upper lobes [22]. In another study of 16 patients with tuberculous pneumonia, consolidations occurred more evenly in the lung lobes, and these patients had more fever, less haemoptysis and shorter duration of disease as compared with patients with cavitary TB [23].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a cohort of 2228 patients with TB in Brazil, 59 (2%) patients presented with noncavitary pulmonary consolidation, which occurred predominantly in the upper lobes [22]. In another study of 16 patients with tuberculous pneumonia, consolidations occurred more evenly in the lung lobes, and these patients had more fever, less haemoptysis and shorter duration of disease as compared with patients with cavitary TB [23].…”
Section: Discussionmentioning
confidence: 99%
“…Even though PTB is a typical chronic disease, it can also present as acute pneumonia [1]. In tuberculous pneumonia (TP), the presentation is usually acute respiratory infection, mainly cough, which precedes other systemic symptoms, and it is often more than two weeks in duration [7]. It is also less severe than other bacterial pneumonia, but hemoptysis is generally rare [8].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of 346 patients hospitalized for CAP, they found out MTB was isolated in 4.9% of cases and the predictive factors that favor PTB are longer duration of symptoms, history of night sweats, upper lobe involvement, cavitary infiltrates, lower total white blood cell count and lymphopenia [9]. Another study of TP also concluded that most cases have consolidation in the upper lobe, with the right lobe predominant [7]. While in atypical CAP, the presentation is usually subacute with progressive constitutional symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Total lung capacity (TLC), inspiratory capacity (IC), expiratory residual volume (ERV), residual volume (RV) and effective resistance (Reff) were recorded. All parameters were expressed as absolute values and as a percentage of predicted for age, height and gender according to the guidelines for pulmonary function tests 19 .…”
Section: Plethysmographymentioning
confidence: 99%